Recidivism amongst children in conflict with the law who have undergone anger management diversion programme: The case of NICRO in Limpopo Province - Mogano, Thapelo Isaac; Rapholo, Selelo Frank; Ramphabana, Livhuwani Bethuel (Technium Social Sciences Journal, 2022)
Studies show that there is a high rate of recidivism amongst children in conflict with the law who have attended anger management programme. Anger management is now a major issue affecting children and youth across societies including South Africa. Poor management of anger often leads children and youth into committing criminal offences. There are no enough studies which rigorously explored possible reasons for children’s reoffending behaviours after attending anger management programme. This qualitative study sought to describe factors which lead children to reoffend after attending anger management diversion programme at NICRO (National Institute of Crime and Re-Integration of Offenders) in Limpopo Province. To pursue the aim of this study, behaviour modification approach was followed. A descriptive multiple case-study design was used to purposefully and conviniently select three social workers who facilitated the programme and ten youths who attended the programme while they were still under the age of 18 years. Semi-structured interviews were used to collect data which was analysed thematically with the assistance of the Nvivo software. Findings revealed lack of family support, peer influence and substance use , poor educational competencies and lack of understanding of the programme as factors leading to recidivism amongst children in conflict with the law. It is therefore recommended that the re-intergration process of children who completed the programme incorporate serious follow up sessions.